Waralaba dalam Perspektif Hukum Islam - Mustofa Mustofa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2017)
Franchising is a trend of effective and efficient business development in the present, because it is very beneficial material can also be a smart solution to minimize the sense of prestige or low self-esteem to sell or entrepreneurship for new graduates or scholars who have just completed their studies. Likewise for beginner entrepreneurs who are still afraid of the loss that is always haunting, Francise is one solution. Apart from being able to bring big and fast profits, it can also bring prestige to the managers. The development of a franchise that is very fast on the ground is expected to raise questions whether the Francise system or franchise is in accordance with Islamic values? In the context of classical fiqh, the term franchise is not known. For this reason, it is necessary to discuss Islamic economic discourse with this franchise pattern, so that we can speak classically: